2-benzothiazoleacetonitrile based two-photon fluorescent probe for hydrazine and its bio-imaging and environmental applications - Jian-Yong Wang (Nature Portfolio, 2017)
Abstract A novel turn-on two-photon fluorescent probe NS-N 2 H 4 was developed with the 2-benzothiazoleacetonitrile as a new recognition site for the detection of hydrazine (N2H4). The two-photon probe exhibited favorable properties including high selectivity, low cytotoxicity and almost 16-fold fluorescence enhancement in the presence of N2H4 in solution. The probe could be used to image hydrazine in the living cells. Notably, we also used the two-photon fluorescent probe to image hydrazine in the tissue imaging for the first time. Furthermore, by the way of probe-loaded TLC plate, we further monitored vapor of hydrazine. Therefore, the novel two-photon probe is expected to be employed to detect N2H4 in biosamples and environmental pollution and the new recognition site will be widely applied to construct fluorescent probes for the detection of N2H4.